2019
DOI: 10.1037/fam0000518
|View full text |Cite
|
Sign up to set email alerts
|

Stepfathers’ affinity-seeking with stepchildren, stepfather-stepchild relationship quality, marital quality, and stepfamily cohesion among stepfathers and mothers.

Abstract: Because of the potential stepparent-stepchild relationships have for tension and conflict, clinicians have identified the development of a positive stepparent-stepchild connection as one of the major tasks of stepfamily life. Stepparents often are advised to focus initially on developing friendships with stepchildren, or seeking affinity with them, particularly early in the life of the relationship. Both family systems theory and evolutionary theory suggest that stepparents’ affinity-seeking behaviors are rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 42 publications
3
38
0
2
Order By: Relevance
“…Factors associated with stepfamily stability that could reasonably be influenced or changed are recommended for inclusion in community education programs. These are (a) recognition and positive acceptance of stepfamilies' unique characteristics or “architecture” (Papernow, ); (b) effective stepparenting practices involving affinity‐seeking (Ganong, Jensen, Sanner, Russell, & Coleman, ) and use of a parenting team that allows for child adjustment to a new parent (Papernow, ); (c) effective coparenting practices with previous partners that maintain a cooperative, low‐conflict environment across households; (d) mutual agreement on roles and rules within the stepfamily (Ganong & Coleman, ); (e) effective financial management skills for navigating the enhanced complexity in stepfamilies (e.g., Higginbotham, Anderson, & Lown, ); (f) effective positive parenting practices between original parent and child(ren) (e.g., Ganong & Coleman, ); and (g) establishment of support network and effective use of outside supports. Suggestions are that enhancements in these cognitive, emotional, and behavioral factors resulting from program attendance will be linked with positive individual outcomes for adults and children, and higher relationship quality and family stability (e.g., Adler‐Baeder, Robertson, & Schramm, ).…”
Section: Relevant Issues and Specialized Content For Stepfamiliesmentioning
confidence: 99%
See 1 more Smart Citation
“…Factors associated with stepfamily stability that could reasonably be influenced or changed are recommended for inclusion in community education programs. These are (a) recognition and positive acceptance of stepfamilies' unique characteristics or “architecture” (Papernow, ); (b) effective stepparenting practices involving affinity‐seeking (Ganong, Jensen, Sanner, Russell, & Coleman, ) and use of a parenting team that allows for child adjustment to a new parent (Papernow, ); (c) effective coparenting practices with previous partners that maintain a cooperative, low‐conflict environment across households; (d) mutual agreement on roles and rules within the stepfamily (Ganong & Coleman, ); (e) effective financial management skills for navigating the enhanced complexity in stepfamilies (e.g., Higginbotham, Anderson, & Lown, ); (f) effective positive parenting practices between original parent and child(ren) (e.g., Ganong & Coleman, ); and (g) establishment of support network and effective use of outside supports. Suggestions are that enhancements in these cognitive, emotional, and behavioral factors resulting from program attendance will be linked with positive individual outcomes for adults and children, and higher relationship quality and family stability (e.g., Adler‐Baeder, Robertson, & Schramm, ).…”
Section: Relevant Issues and Specialized Content For Stepfamiliesmentioning
confidence: 99%
“…Given that their heritage emphasizes familism, traditionalism, and religiosity (e.g., Landale, Oropesa, & Bradatan, ; Vega, ), Latin American stepfamilies may be more likely to adopt first family roles as stepfamily members (Berger, ). Thus, Latinx stepfamily members report having difficulty with involving nonresidential biological parents (Skogrand et al, ) and can feel challenged by the recommendation based on studies of stepfamily dynamics that stepparents should ease into a parenting role (Ganong et al, ; Hetherington & Stanley‐Hagan, ). Because of cultural expectations, noncustodial biological Latinx parents may withdraw from their parental role and the stepparent may assume a primary parental role more quickly (Skogrand et al, ).…”
Section: Moving the Stepfamily Education Field Forwardmentioning
confidence: 99%
“…According to Ganong et al (2019) attempting to create a positive stepparent-stepchild relationship is a significant task toward family development. The researchers examined the perceptions of stepfathers and biological mothers' infinity seeking.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In summary, stepfathers affinity seeking played a significant role in their perceptions (Ganong et al, 2019); Pink & Wampler found stepfamilies needed the most assistance around specific areas such as: cohesion, feelings of togetherness, adaptability, and problem solving; it was found that children who had suffered economic or social loss faired worse emotionally Meggliolaro, Ongaro & Whiteside) found inviting various family members to family functions led to inclusivity which then led to cohesion and positive adjustment to new norms. On the other hand, children who had family members that were cut off from family rituals faired more negatively which led to negative emotional energy which then lessened cohesion; Jensen, et al found that transitions within stepfamily formation can be stressful for parents and children; and lastly, Degreef & Platt found that third parties may attempt to sabotage newly reconstituted families which then may lead to resentment of the new parental figure.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The presence of resident stepchildren can lead to parenting difficulties for stepparents and increased risk of marital dissolution (Beaudry et al, 2004). Although studies have shown that stepfathers' affinity-seeking behaviour is associated with less conflict with their stepchildren, better couple relationships and closer family ties (Ganong et al, 2019b), the success of these efforts varies and likely depends partly on the receptivity of the stepchildren (Stern, 1982;Ganong et al, 1999;Ganong et al, 2011).…”
Section: Remarriages and Stepfamiliesmentioning
confidence: 99%